Diet quality and weight status of adult women at Tuba Island, Langkawi, Malaysia / Nazrul Hadi Ismail ... [et al.] - Ismail, Nazrul Hadi; Khairi, Nur 'Ainaa Farhana; Abd Hamid, Syahrul Bariah; Kamarul Zaman, Mazuin; Ahmad Shuhaimi, Farhanah (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
The prevalence of overweight and obesity in rural regions is high due to low income and limited access to nutritious foods. It is contributed by the geographical factor, which limits access to the availability of nutritious foods. Thus, this study aimed to determine the prevalence of weight status, diet quality, and its association among adult women in Tuba Island. This cross-sectional study was administered thru a structured questionnaire consisting of sociodemographic characteristics, 24-hour diet recall, and the Malaysian Healthy Eating Index (HEI). Weight and height were measured. HEI was used to identify the level of diet quality in the population. A total of 114 respondents aged between 18 to 45 years old were involved. 43% (n=49) and 26.3% (n=30) of them were overweight and obese respectively. While 28.1% (n=32) had normal weight status. The mean score of HEI was 42.44 ± 7.49, indicating poor diet quality. Further investigation showed they had poor compliance to meet dietary guidelines for vegetables, fruits, legumes, and milk and milk products. Nonetheless, diet quality was not associated with weight status in this population. The present study showed that more than half of the adult women at Tuba Island were overweight and obese, and their diet quality was poor.